2016
DOI: 10.1155/2016/8382469
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Load in Daily Urine Samples of Patients Infected withMycoplasma genitalium, Mutation Analysis, and Response to Treatment

Abstract: Objective. Increasing macrolide resistant strains of Mycoplasma genitalium is a challenge, and to differentiate between treatment failure and reinfection a timely test of cure (TOC) is warranted. The aim of this study was to evaluate the best time for TOC after five days' treatment of Mycoplasma genitalium infection with azithromycin. Methods. Nineteen patients with positive PCR for Mycoplasma genitalium in urine provided urine samples daily for 2 weeks and on days 21, 28, and 35. Samples were tested by a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(43 reference statements)
2
6
0
Order By: Relevance
“…For swabs, the load of genomes per swab ranged from 27.9 (log 10 load, 1.45) to 9.3 ϫ 10 6 (log 10 load, 6.97), with a median of 6.8 ϫ 10 3 (log 10 load, 3.83). This large variation of load is similar to reports examining male first-void urine and urethral specimens (8) and urine specimens in men and women undergoing treatment (range, 49.6 to 7.28 ϫ 10 5 bacteria per milliliter) (12).…”
Section: Resultssupporting
confidence: 85%
“…For swabs, the load of genomes per swab ranged from 27.9 (log 10 load, 1.45) to 9.3 ϫ 10 6 (log 10 load, 6.97), with a median of 6.8 ϫ 10 3 (log 10 load, 3.83). This large variation of load is similar to reports examining male first-void urine and urethral specimens (8) and urine specimens in men and women undergoing treatment (range, 49.6 to 7.28 ϫ 10 5 bacteria per milliliter) (12).…”
Section: Resultssupporting
confidence: 85%
“…Twenty-five studies and 4003 samples, collected in 16 countries between 2005 and 2017, were included in the meta-analysis of fluoroquinolone resistance-associated mutations (Table 1). Most (58•5%) samples were from 10 European, 22,25,27,31,[33][34][35] (mainly Nordic) (23•0%), 38,39,48 countries and from the Western Pacific (35•1%) 11,53,[58][59][60][61]63,76,77 mainly Japan (18•4%) 11,[58][59][60]63,77 and Australia (15•0%). 53,76 In the Americas, samples were collected in USA and Canada (6•1%).…”
Section: )mentioning
confidence: 99%
“…We identified an M. genitalium persistence rate of 21% up to 12 months, which is disconcerting given the high prevalence rate in our population and the morbidity associated with M. genitalium in women. This could still be an underestimate, however, because another 38% had mixed infections, and intermittent negative results could have represented fluctuations in bacterial loads below the limit of detection [32]. Although pathogen persistence could indicate long-term colonization of the female genital tract, McGowin et al [33] demonstrated that persistent M. genitalium elicits chronic inflammatory cytokine secretion in endocervical epithelial cells, even when there are low organism burdens associated with asymptomatic infections.…”
Section: Clearance and Persistence Of M Genitalium Infectionmentioning
confidence: 99%